A new Charopidae from Chile and Argentina, Stephacharopa calderaensis n. gen. and n. sp., with remarks on the taxonomy of the genus Stephadiscus Hylton Scott 1981 - Miquel, Sergio Eduardo (2013)
A new genus and new species of Charopidae, Stephacharopa calderaensis, is described based on specimens collected in the Atacama region, northern Chile. The new genus is clearly distinct from its confamilial genera due to its axial shell sculpture. The new genus also includes the spe- cies Stephacharopa testalba (Hylton Scott 1970) n. comb. and Stephacharopa distincta (Hylton Scott 1970) n. comb. The related genus Stephadiscus Hylton Scott 1981 is herein redefined. . Species thus included in genus Stephadiscus are S. lyratus (coutHouy in gould 1846), S. rigophila Mabille 1886, S. perversus (Hylton Scott 1969), S. rumbolli (Hylton Scott 1973) and S. stuar- doi Miquel & barker 2009, all of them with a distribution restricted to humid areas of southern South America.